PENGARUH PEMBERIAN TEPUNG BUAH DAN DAUN MENGKUDU (Morinda citrifolia) TERHADAP PRODUKTIFITAS AYAM PETELUR FASE LAYER - Miarsono Sigit; Rohmad .; David Zuni Abrianto (Jurnal Ilmiah Fillia Cendekia, 2017)
Research on "The Effect of fruit and mud crab (Morinda citrifolia) powder on layer productivity" has been carried out on 07 April to 12 mei 2017 in Beji village, Boyolangu sub district, Tulungagung district. The purpose of this study was to determine the effect of giving fruit powder and leaf to layer laying chicken productivity. The material used in this research is laying chicken type isa brown age 25 weeks with amount of 96 head and treatment of fruit flour and noni leaf which put into capsule with dose (0,6 g, 1,2 g and 1,8 g / chicken). The data obtained will then be analyzed by using the factorial RAL factorial analysis and forwarded by Duncan's multiple range test with a significant level of 5%. Based on the result of the research, it can be concluded that the giving of noni fruit flour able to decrease feed consumption and able to increase egg weight at level 2 (1,2 g / chicken), but do not give effect to egg yolk color. Egg yolk at level 2 (1.2 g / chicken) ,, but did not give effect to feed consumption and egg weight.